Super Resolution Imaging Needs Better Registration for Better Quality Results - Varsha Hemant Patil; Kharate G K; Kamlapur Snehal Mohan (Institute of Advanced Engineering and Science, 2012)
In this paper, trade-off between effect of registration error and number of images used in the process of super resolution image reconstruction is studied. Super Resolution image reconstruction is three phase process, of which registration is of at most importance. Super resolution image reconstruction uses set of low resolution images to reconstruct high resolution image during registration. The study demonstrates the effects of registration error and benefit of more number of low resolution images on the quality of reconstructed image. Study reveals that the registration error degrades the reconstructed image and without better registration methodology, a better super resolution method is still not of any use. It is noticed that without further improvement in the registration technique, not much improvement can be achieved by increasing number of input low resolution images.